PSYCHOLOGICAL WELL-BEING RELATIONS WITH HYPERTENSION - Achwandi, Moch. Achwandi; Khusniyah, Zulfa (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2024)
Stressors in life contribute to a person's blood pressure values. High blood pressure can be suffered if you are less able to adapt to these various stressors. Currently hypertension has become a major problem in world health. Based on Riskesdas 2018, the prevalence of hypertension in Indonesia is 34.1%. The aim of this research is to analyze the relationship between Psychological Well-Being and the Degree of Hypertension. This research is a correlational analytical with a cross sectional approach. Sampling used purposive sampling. The instruments used were the PWBS from Ryff and the degree of hypertension according to WHO. Data analysis used the Spearman Rho test with the results of the analysis obtained p value = 0.000 (α = 0.05) and correlation coefficient = 0.708. There is a significant relationship between Psychological Well-Being and the respondent's degree of hypertension, with the strength of the relationship being strong and the direction of the relationship being positive, which means that the higher the Psychological Well-Being, the degree of hypertension or blood pressure is in the high normal category. It is hoped that respondents can carry out 10 behaviors that can increase Psychological Well-Being so that they can reduce the risk of hypertension.